The Impact of Mind Mapping on Science Learning on Student Learning Outcomes - Waliyah, Waliyah; Solikin, Asep (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Science learning in schools has long focused predominantly on products such as facts, laws, and theories, with limited attention to processes and attitudes. This approach often results in students struggling to understand concepts and apply them in real-life contexts. In response, Aim: this study aims to examine the application of the Mind Mapping strategy in science learning to improve students’ cognitive and affective outcomes, particularly on the topic of ecosystems. Method: The research employed a descriptive qualitative method involving 27 seventh-grade students at SMP Negeri Satap 8 Bulik in the 2023/2024 academic year. Data were collected through pre-tests, learning activities, post-tests, and interviews with teachers and students, and analyzed through data collection, reduction, presentation, and conclusion drawing. Results and discussions: The results showed that learning management using the Mind Mapping strategy was well executed, supported by validated learning tools. Cognitive outcomes achieved 100% classical mastery, while affective outcomes reached 80.6%, slightly below the Merdeka Curriculum target. Students responded very positively, with the majority perceiving Mind Mapping as enhancing creativity, focus, and material retention. However, challenges included limited time allocation and difficulty in translating ideas into visual form. Conclusion: Overall, the implementation of Mind Mapping positively influenced students’ engagement and learning outcomes, demonstrating its potential as an effective approach to science instruction.